1993
DOI: 10.1111/j.1440-1584.1993.tb00076.x
|View full text |Cite
|
Sign up to set email alerts
|

The University of Sydney Rural Careers Project

Abstract: This article describes the activities of the University of Sydney Rural Careers Project, which was established to increase the opportunities for undergraduate students in the health professions to learn more about what it is like to live and work within a rural community. After 18 months of operation, the project has attracted wide support among students and staff, and could be seen as a model worth replicating in other universities. Stimulating interest in rural practice may increase the numbers of health pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 2 publications
1
3
0
Order By: Relevance
“…The suggestion that, from an undergraduate’s viewpoint, the advantages of rural practice are overwhelmed by the disadvantages 1 was not borne out by this study. Our results agree with a previous study which found early short exposure to rural practice had a positive effect on students’ attitudes 3 . The differences we found between rural and non‐rural students in their uptake and response to the placement are commensurate with rural students being more likely to practise in rural areas.…”
Section: Discussionsupporting
confidence: 92%
“…The suggestion that, from an undergraduate’s viewpoint, the advantages of rural practice are overwhelmed by the disadvantages 1 was not borne out by this study. Our results agree with a previous study which found early short exposure to rural practice had a positive effect on students’ attitudes 3 . The differences we found between rural and non‐rural students in their uptake and response to the placement are commensurate with rural students being more likely to practise in rural areas.…”
Section: Discussionsupporting
confidence: 92%
“…Added perceived benefits from IP practice education included the improvement of the working environment for providers 11 , gaining role clarity and greater comfort in working with interdisciplinary teams 1,8,13 , and familiarity with underserved communities 13,25 . IP training may also lessen professional isolation and conflict between the professions as argued by Hays et al 28 . While teamwork or collaborative practice has become important to provide better patient care regardless of location 6,24 , the consequences of not collaborating may be more disastrous in rural areas 9 .…”
Section: Evaluating the Interprofessional Componentmentioning
confidence: 99%
“…The following is a brief description of several examples of educational sessions that could provide enjoyable, shared learning among varying combinations of health professional students. The author has had experience with all these, usually just with medical students, although some were designed to become multi‐professional and the rural theme activity was broadly multi‐professional 5 . Successful initiatives elsewhere, with medicine and pharmacy students, and medicine and allied health students, have been described 6,7 .…”
Section: Examples Of Ipementioning
confidence: 99%